EXTRACTION AND PHYSICO-CHEMICAL PARAMETER ANALYSIS OF DESERT DATE (Balanite aegyptiaca) OIL FROM DUTSIN-MA - Kabo, Kamaluddeen Suleiman; Ali, Tijjani; Ogbesejana, Abiodun B. (FUDMA JOURNAL OF SCIENCES, 2020)
Desert date (Balanites aegyptiaca) is perennial plant with a variety of application in vegetable oil, food preparation, condiment and medicine. This work covers extraction and physico-chemical parameters analysis: acid value, iodine value and saponification value of Balanite aegyptiaca seed oil samples obtainable at Dutsin-Ma Area, Katsina State. Soxhlet extraction method was used in order to extract oil from the samples followed by its analysis according to standard protocols. The result shows that the seeds have high oil content, percent yield of 39.58% with the density of 0.91 g/cm3, acid value 2.66, iodine value 98.74 g/100g, saponification value of 186.5 mgKOH/g and low moisture content of 2.6% was obtained. This shows that the seeds of Balanite aegyptiaca oil of Dutsin-Ma local area have high oil yield and good qualities making it suitable for use in a variety of applications to improve its value chain